Identification of the demographic, temporal and geographical risk factors for road traffic injuries (RTIs) in the State of Qatar: An analysis of health sector (ambulance, emergency and trauma) data on RTIs - Lawrence Tallon (19774581) (2015)
The 1.2 million deaths per annum globally caused by road traffic injuries (RTIs) have been likened to a plane crashing every day (1). Nevertheless, RTIs are a neglected public health concern. There were 247 road traffic fatalities in Qatar in 2010, a rate of 14.4 deaths per 100,000 people. Even though recent progress has been made, this remains three times higher than Western European countries. It is akin to a plane crash every year for Qatar. This study builds on previous analyses of death rates from RTIs in Qatar (2). However, deaths represent less than 3% of all RTIs. This study uses the much larger sample size of all RTIs for 2014. It triangulates three important sources of health sector data: ambulance, emergency department and trauma registry. It analyses 13,000 patient episodes and deconstructs in more detail than heretofore the epidemiology of RTIs in Qatar. The results identify the key demographic, temporal and geographical features of this public health emergency. Qatari males aged 15-19 have a relative risk of RTI 8-11 times higher than the general population and those aged 20-24 have a relative risk 6-9 times higher (see chart for illustration). RTIs in those aged 25 and above are overwhelmingly in non-Qataris and vary substantially in type of road use between the other Arabic and South Asian resident populations. The results also identify the temporal and seasonal effects associated with RTIs and a “heat map” of the accident “hot spots” by geographical zone. It is possible to identify with a high degree of probability which road users are most at risk of harm, when and where. Using recent insights into how predictive data is used by the insurance industry, health policy makers may be able to more effectively target regulatory, technological and behavioural interventions to those most at risk. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.4